The AHA/ACC/HFSA 2022 Heart Failure Guidelines: Changing the Focus to Heart Failure Prevention - Arielle Abovich; Daniel S. Matasic; Rhanderson Cardoso; Chiadi E. Ndumele; Roger S. Blumenthal; Ron Blankstein; Martha Gulati (Elsevier, 2023)
The prevalence of heart failure (HF) in the United States (U.S.) is estimated at over 6 million adults, with the incidence continuing to increase. A large proportion of the U.S. population is also at risk of HF due to the high prevalence of established HF risk factors, such as hypertension, diabetes, and obesity. Many individuals have multiple risk factors, placing them at even higher risk. In addition, these risk factors disproportionately impact various racial and ethnic groups. Recognizing the rising health and economic burden of HF in the U.S., the 2022 American Heart Association / American College of Cardiology / Heart Failure Society of America (AHA/ACC/HFSA) Heart Failure Guideline placed a strong emphasis on prevention of HF. The purpose of this review is to highlight the role of both primary and secondary prevention in HF, as outlined by the recent guideline, and address the role of the preventive cardiology community in reducing the prevalence of HF in at-risk individuals.